GAMBARAN KUALITAS TIDUR DAN ZAT GIZI MIKRO DENGAN TEKANAN DARAH PADA PEKERJA SHIFT (Studi Pada Perawat RSJD Dr. Amino Gondohutomo Semarang) - Vika Agustin Damayanti; Ari Udiyono; Lintang Dian Saraswati; Praba Ginandjar (Jurnal Kesehatan Masyarakat (Undip), 2018)
Sleep disorders in adults occur about 20-40% annually. Changes in work schedules (shift work) as a predictor of sleep disorders accounted for 2-5%. If it happens for years it will have an impact on blood pressure. In addition, potassium and sodium intake as the main cation in the body's extracellular fluid can also affect blood pressure levels. The purpose of this study is to describe the quality of sleep, sodium and potassium intake with blood pressure in nurses shift RSJD Dr. Amino Gondohutomo Semarang. The type and design of this study is descriptive with a cross-sectional approach conducted in October 2017 with a total sample of 108 nurses shift. This research used interview method and blood pressure measurement. The result showed 48.1% respondent characteristic were in the age group 26-35 years, 69,4% female, 40,7% worked on morning shift, 37% afternoon shift, and 22,2% night shift. As many as 50.9% of respondents began to experience the blood pressure of the blood pressure status is already on the Pre Hypertension. As many as 28,7% of respondents have poor sleep quality. There are 3 components that contribute many PSQI score that is sleep latency, sleep duration, and sleep disturbance. Of the three components that most contribute the score is sleep disturbance. As many as 86,1% of respondents had less sodium intake, and 96,3% had less potassium intake. It is expected that the nurse can maximize the rest time as possible and it is recommended to consume foods containing sodium and potassium to balance blood pressure.